General concepts in nanoparticle technology and their possible implication on cultural science and philosophy - Peukert, Wolfgang (Powder Technology, 2005)
This paper consists of two parts. The first part describes generally applicable concepts in nanoparticle technology. A key objective in nanotechnology is to build functional structures from small building blocks, i.e. nanoparticles. Starting from the concept of product engineering we investigate the basic preconditions for tailoring functional structures and their properties. Formation of macroscopic structures is only possible through microscopic control of particulate interfaces, i.e. of particle interactions. Particle interactions result mainly from the molecular properties of the respective surfaces which are governed by quantum mechanics. However, in many cases particle interactions can be sufficiently described by classical force laws. The sum of all these forces plus external forces leads to the desired structure. The second part of this paper draws conclusions from these physical principles and dares to apply these to philosophy and cultural sciences. It seems that encounters between entities, in this case individuals, small groups, countries, for instance, leads to the development of social structures and in most general sense to culture. Changing the interactions between the entities will lead to different structures. The conclusion is straightforward but extremely complex in general: We as individuals are tailoring life and culture by our way of interacting. © 2005 Elsevier B.V. All rights reserved.
Keywords: Cultural sciences; Nanoparticles; Philosophy; Product engineering; Structure formation